2012
DOI: 10.1515/1553-3840.1623
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antioxidant and Vasodilating Activities of Gmelina arborea (Verberaceae) Leaves Hexane Extract

Abstract: The present study investigated the effects of Gmelina arborea hexane leaves extract on markers of oxidative stress and its vasorelaxant effects on isolated rat aorta, in order to postulate the possible mechanisms involved in the antihypertensive properties of the plant. To evaluate the antioxidant effects of the extract, rats were randomly divided into four groups of five rats each. With the exception to the group receiving Tween (2.5%), the other groups were treated either with NaCl (900mg/kg/day) alone, NaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The extract of Globularia alypum (GA) also relieved diastolic PHE (2–4 ng mL −1 )-induced mesenteric artery contractions in rats, which was inhibited by endothelial removal or atropine, but not indomethacin (10 μM) or L-NAME (100 μM) ( Chokri et al, 2012 ). The extract of Gmelina arborea hexane leaves (GAE) produced vasodilatory effects in PHE (1 μM)-induced contractions which was reduced by L-NAME (2 μM), indomethacin (2 μM) and glibenclamide (2 μM) ( Wansi et al, 2012 ).…”
Section: Traditional Medicinal Plants With Vasodilation In mentioning
confidence: 99%
“…The extract of Globularia alypum (GA) also relieved diastolic PHE (2–4 ng mL −1 )-induced mesenteric artery contractions in rats, which was inhibited by endothelial removal or atropine, but not indomethacin (10 μM) or L-NAME (100 μM) ( Chokri et al, 2012 ). The extract of Gmelina arborea hexane leaves (GAE) produced vasodilatory effects in PHE (1 μM)-induced contractions which was reduced by L-NAME (2 μM), indomethacin (2 μM) and glibenclamide (2 μM) ( Wansi et al, 2012 ).…”
Section: Traditional Medicinal Plants With Vasodilation In mentioning
confidence: 99%
“…Indeed, in vitro study on rat aortic rings showed a vasorelaxation effect of G. arborea, which is, in part, NO dependent (Wansi et al, 2012). G. arborea extract could thus act by reversing the inhibiting effect of L-NAME on NO synthase.…”
Section: Resultsmentioning
confidence: 98%
“…arborea extract induced a significant reduction of blood pressure when administrated to rats following 7 days treatment with L-NAME or during the 7 last days of a 14-days treatment with L-NAME. In a previous study investigating the effect of aqueous extract of G. arborea on a salt-induced hypertension in rat, single dose intravenous administration of the extract induced a dose dependent but transient decrease of rat blood pressure (Wansi et al, 2009). As the measurement of blood pressure 24 h after the last administration of L-NAME, the study data showed that repeated oral administration of G. arborea leaves extract could induce not only a transient, but also a sustained decrease of blood pressure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gmelina arborea (White teak) is one of such plants and belongs to the Verbinaceae family. It has been screened and reported to possess derived compounds that have beneficial effect on immunity, fertility, antioxidant defence, increased metabolic activity, detoxifying and cleansing properties (Wansi et al, 2012). Therefore, investigations into the pharmacological validation of this less explored plant will go a long way in handling physiological and reproductive defects in animals arising from Cd toxicity through ingestion or inhalation.…”
Section: Introductionmentioning
confidence: 99%